Direct and Indirect Influence of Financial Factors through Environment, Social, Governance (ESG) Disclosure on Firm Value for Firm Sustainability - Machmuddah, Zaky; Utomo, Dwiarso (Journal of Ecohumanism, 2024)
The purpose of this study is to explore the direct and indirect effects of financial factors through Environment, Social, Governance (ESG) disclosure on firm value. The population of this research is all companies in Asian countries which are registered in the integrated reporting examples database. After going through the specified sample selection stage, 225 data were obtained. This data was obtained from secondary data for each company from 2017-2021. The analytical tool used in this study is WarpPLS. The results of this study indicate that firm size and profitability directly affect firm value, but leverage does not affect firm value. In addition, firm size and leverage also have an effect on ESG disclosure, but profitability has no effect on ESG disclosure. Primarily ESG disclosure mediates the influence of financial factors, namely firm size, profitability and leverage on firm value. The implication of this research is the importance of companies increasing firm value because it is the basis for investors’ decision making in investing. To increase the firm value, companies must pay attention to both financial and non-financial factors such as ESG disclosure, because investors are getting smarter in making decisions not only based on financial factors, but also non-financial factors, especially ESG disclosure to maintain the company’s sustainability. This study can also be used as a basis for formulating policies for regulators in Asian countries to improve corporate sustainability practices. arThe originality of this study is placing ESG disclosure as a mediating variable between the effect of a company’s financial performance on firm value.